Design and Synthesis of Some (S)-2-(6-Methoxynaphthalen-2-yl)-N-substituted Ethyl Propanamide Derivatives as Potent Non-ulcerogenic Anti-inflammatory and Analgesic Agents - Berk, Barkin; Erol, Dilek Demir; Kupeli, Esra; Yesilada, Erdem (Arzneimittelforschung, 2009)
The carboxylic acid group of the antiinflammatory drug, (S)-2-(6-methoxy-naphthalen-2-yl) propanoic acid, naproxen (CAS 22204-53-1) was reacted with the substituted ethylamine derivatives to form (S)-2-(6-methoxynaphthalen-2-yl)-N-substituted ethyl propanamides by using N,N’-dicyclohexyl carbodiimide (DCC) and 4-(dimethylamino) pyridine (DMAP). Anti-inflammatory and analgesic activities of the compounds were assessed in vivo by carrageenan-induced hind paw edema and p-benzoquinone induced abdominal contraction tests in mice, respectively. In addition, the ulcerogenic properties of the new compounds were evaluated, and compared to that of naproxen. Among the newly synthesized compounds, compound 2f showed the highest analgesic and antiinflammatory activity at 100 mg/kg oral dose, without inducing any gastric lesion. Although this compound induced less gastric lesions than naproxen, it was found to have less anti-inflammatory and analgesic activity when compared to indometacin (CAS 53-86-1). These new compounds therefore deserve further attention to develop new lead drugs.
Keywords: Analgesics; Antiinflammatories; CAS 53-86-1; CAS 22204-53-1; Ethyl propanamide derivatives; Naproxen; Ulcerogenesis